2021
DOI: 10.1155/2021/3919989
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty Improved Locomotive Syndrome in Knee Osteoarthritis Patients: A Prospective Cohort Study Focused on Total Clinical Decision Limits Stage 3

Abstract: Purpose. The purpose of this study is to investigate the treatment efficacy of total knee arthroplasty (TKA) on locomotive syndrome (LS) focusing on total clinical decision limit (CDL) stage 3 leading to revealing the motor function indicators that can predict LS improvement in knee osteoarthritis patients who had received TKA. Methods. This prospective cohort study was conducted in 47 patients evaluated as total CDL stage 3 before TKA who received primary TKA on the operated side and were diagnosed with Kellg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…KOA is one of the common joint diseases in the elderly and it is also the main cause of knee pain and functional limitation in the elderly [ 34 , 35 ]. TKA is a relative successful and effective method for relieving pain and functional recovery of end-stage knee osteoarthritis, which has been widely carried out worldwide [ 9 , 36 ]. Reconstruction of good lower limb alignment is one of the main purposes of TKA, and it is also an important guarantee of patient satisfaction and prosthesis survival rate after TKA [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KOA is one of the common joint diseases in the elderly and it is also the main cause of knee pain and functional limitation in the elderly [ 34 , 35 ]. TKA is a relative successful and effective method for relieving pain and functional recovery of end-stage knee osteoarthritis, which has been widely carried out worldwide [ 9 , 36 ]. Reconstruction of good lower limb alignment is one of the main purposes of TKA, and it is also an important guarantee of patient satisfaction and prosthesis survival rate after TKA [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of KOA is expected to be on the rise due to the expanding aging population [ 3 ]. Total knee arthroplasty (TKA) is the best method for the treatment of late-stage KOA [ [9] , [10] , [11] , [12] ]. In China, over 370,000 TKAs were performed each year with an annual growth rate of 15% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 The prevention and treatment of LS included exercise, 13 nutrition, 14,15 and total joint arthroplasty. [16][17][18] For exercise or nutrition, improving motivation is one of the most important issues. A concern was that having a higher Locomo Age than expected would decrease the patients' motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that as LS stages progressed, the risk of falls increased, 10 the quality of life decreased, 11 and mortality increased 12 . The prevention and treatment of LS included exercise, 13 nutrition, 14,15 and total joint arthroplasty 16–18 . For exercise or nutrition, improving motivation is one of the most important issues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that surgical treatment of knee joint [13] and hip joint disease [3] can improve the condition of patients in CDL Stage 3, but there have been few reports on lumbar degenerative diseases. Therefore, this study aimed to investigate the efficacy of lumbar spinal surgery for patients with LSS in CDL stage 3 and the preoperative factors associated with the improvement of the CDL stage.…”
Section: Introductionmentioning
confidence: 99%